Liver transplantation is beneficial regardless of cirrhosis stage or acute-on-chronic liver failure grade: A single-center experience - Cervantes-Álvarez, Eduardo; Vilatoba, Mario; Limón-de la Rosa, Nathaly; Méndez-Guerrero, Osvely; Kershenobich, David; Torre, Aldo; Navarro Álvarez, Nalu (My University, 2022)
Background: Liver transplantation for the most critically ill remains controversial; however, it is currently the only curative treatment option. Aim: To assess immediate posttransplant outcomes and compare the short (1 year) and long-term (6 years) posttransplant survival among cirrhotic patients stratified by disease severity. Methods: We included cirrhotic patients undergoing liver transplantation between 2015 and 2019 and categorized them into compensated cirrhosis (CC), decompensated cirrhosis (DC), and acute-on-chronic liver failure (ACLF). ACLF was further divided into severity grades. Our primary outcomes of interest were total days of intensive care unit (ICU) and hospital stay, development of complications and posttransplant survival at 1 and 6 years. ©The Author(s) 2022. Published by Baishideng Publishing Group Inc. All rights reserved.
Keywords: Acute-on-chronic liver failure; Critical care; Liver transplantation; Prognosis; Survival analysis